The Role of Muhammadiyah in Enhancing Digital Literacy in Educational Settings: A Study at Universitas Muhammadiyah Sidenreng Rappang - Rasyid, Rustam Efendy; Aisa, Sitti (Jurnal Ilmiah Global Education, 2025)
This research explores the role of Universitas Muhammadiyah Sidenreng Rappang in developing digital literacy among lecturers and students, an increasingly critical competence in modern education. The study aims to identify the extent to which university-provided facilities, training, and policies enhance lecturers' digital competencies and to evaluate the impact of these policies on students’ learning experiences, including existing challenges and disparities. Employing a qualitative approach based on Creswell’s (2014) framework, data were gathered through interviews, questionnaires, observations, and documentation using purposive sampling involving university leaders, lecturers, and digital learning coordinators. Thematic analysis was conducted to identify patterns related to digital literacy development. Findings reveal that the university has made significant progress, with most lecturers rating the facilities and training as excellent or good, and reporting improvements in teaching quality. However, gaps remain in policy communication and equitable access to digital tools. Student responses also showed positive perceptions, though uneven access, limited participation, and suboptimal program outcomes indicate the need for improvement. The study implies that to fully realize the benefits of digital literacy, the university must enhance infrastructure, refine training programs, and strengthen policy outreach to ensure inclusive and effective